Importance of Clinical Examination in Dentoalveolar Trauma - Marao, Heloisa Fonseca; Barioni, Sônia Regina Panzarini [UNESP]; Manrrique, Gustavo Rodrigues; Luvizuto, Eloa Rodrigues; Melo, Moriel Evangelista [UNESP] (Lippincott Williams & Wilkins, 2012)
Dental injuries are often the result of direct trauma. The most affected teeth are the upper incisors, and the most frequent lesions are coronal fractures, contusions, and lip and alveolar mucosa lacerations. The objective of this study was to draw attention to the importance of the correct management of cases of crow fractures associated with soft tissue lacerations when the fragment is not located. This is a clinical case of crown fracture, the fragment of which remained lodged inside the lip. After fragment removal, the clinical case showed a satisfactory repair emphasizing the importance of a meticulous clinical examination to achieve a correct diagnosis and an appropriate treatment plan, which is essential for a favorable prognosis.
Keywords: Tooth fractures; soft tissue injuries; tooth injuries